Architecture and School: an approach about physical and educational space in teaching processes/Arquitetura e Escola: uma abordagem do espaço físico educacional colaborador dos processos de ensino - Jaciel Guilherme da Silva; Conceição Maria Dias de Lima; Claudia Cristina Rêgo Almeida (Universidade Estadual de Alagoas, 2020)
Primary childhood education, as a social promoter, has required the elaboration of spaces in which everyone has access, and this has significantly altered the functioning of these institutions. The adequacy of school spaces (not yet accessible) to improve training processes shows degraded institutions, in terms of physical, functional and / or accessibility, showing spaces that collaborate with distraction and learning. The development pedagogical work influencing the objectives of the children's learning process. This work investigated the necessity for architectural projects for childhood education, listing indispensable data for the design of these spaces; characterize new perceptions about the physical design of early childhood education institutions, as well as their functionality, based on RECNEIs with respect to the requirements of an appropriate architectural design. The environment influences the people react to it; thermal, luminous, acoustic, decorative can be key pieces to collaborate or hinder teaching-learning processes. The school aesthetic and functional prominence, but its end should not be architectural monumentality; Does not matter having schools without functionality consistent with their main purpose.